Project of life in medicine students of a public university - Izaguirre Sotomayor, Manuel (2021)
Introduction. The life project as a teaching tool will help the medical student to develop a vision for the future to ensure their stay in college, assuming that the profession is not the end but the means to make your dream of a better future reality for him, his family and society, with satisfactory academic results, lower rates of disapproval and dropout, by improving his ability to make decisions. Objectives. Know the life project, dreams, visions and goals of the sixth year students of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos. Methods. Observational, descriptive, cross-sectional, with a quantitative approach, using an open-question questionnaire as an instrument. Results. 94% said they have a life project, 98% have dreams, 96% have vision and 76% have short and long term goals. 52% had as a dream finish the race, residence and successful specialty, practice the profession, have a family and travel. 86% stated that they had the vision of being a good professional, a good specialist, an entrepreneur, working in the state, being a teacher, a researcher, having a family, traveling, having their own home and being happy. Conclusions. In the medical students of the sixth year of the Faculty of Medicine UNMSM, 94% reported having life project, 98% have dreams, vision 96%, and 76% have goals short and long term.